How to Achieve Diversity, Equity, and Inclusion in The Korean Society of Gastroenterology? - Nayoung Kim; Kwangwoo Nam; Ki-Nam Shim; Hyo Jung Kim; Su Youn Nam; Sae Kyung Joo; Seun Ja Park; Yonghoon Choi; Yoon Ju Jung; Yong Sung Kim; Ja Kyung Kim; Seon Mee Park (The Korean Journal of Gastroenterology)
With the increasing emphasis on diversity, equity, and inclusion (DEI) in organizations and institutions, academic societies in gastroenterology and hepatology are beginning to take actionable steps toward achieving DEI. The successful implementation of DEI initiatives leads to excellence in the field, improved patient outcomes, particularly in areas where health disparities are prevalent, and advances in the gastrointestinal discipline. Such implementation also results in a workforce that better reflects the growing diversity of the population. This review defines DEI and introduces the DEI policies and strategies adopted by the academic societies of gastroenterology in other countries. This paper proposes strategies to integrate DEI better into the Korean Society of Gastroenterology, emphasizing the importance of embedding DEI into the culture and strategic framework. The key strategies include establishing a DEI committee, setting clear targets, and conducting formal assessments to measure DEI progress. This study focused on enhancing workforce diversity, particularly among women and young doctors, and advocates for the need to support their academic development through male allyship and the promotion of equitable and inclusive academic cultures.